2021
DOI: 10.7440/res78.2021.03
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Indigenous Communities in Latin America: A Comparative Analysis of State Public Policy Strategies in Mexico, Bolivia, and Colombia

Abstract: The arrival and ongoing consequences of the COVID-19 pandemic during 2020 and 2021 have exacerbated issues related to processes such as globalization, transnational migration, and socioeconomic, educational, and territorial marginalization experienced by indigenous communities throughout Latin America. This article examines the ways in which the State has managed the pandemic in indigenous communities by analyzing individual case studies selected from three countries in the region (Mexico, Bolivia, and Colombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Territorial inequalities reflect the limitations suffered by indigenous populations in the exercise of their rights. Modernity in the region and the growth of the agricultural frontier have led to displacement, but international pressure has halted these processes [74]. A decade ago, more than 50% of the indigenous population of Brazil and Colombia experienced forced migration processes, and these peoples had an important interrelationship with urban areas [70].…”
Section: The Current Situation Of Indigenous People In Latin Americamentioning
confidence: 99%
See 2 more Smart Citations
“…Territorial inequalities reflect the limitations suffered by indigenous populations in the exercise of their rights. Modernity in the region and the growth of the agricultural frontier have led to displacement, but international pressure has halted these processes [74]. A decade ago, more than 50% of the indigenous population of Brazil and Colombia experienced forced migration processes, and these peoples had an important interrelationship with urban areas [70].…”
Section: The Current Situation Of Indigenous People In Latin Americamentioning
confidence: 99%
“…In the area of social policy, 29 Latin American countries have adopted 285 social protection measures to help households suffering from the greatest poverty, vulnerability, and insecurity. The most frequent measures have been cash transfers and the provision of food (41.8% and 19.3% of the total, respectively), but it is not possible to know what the impact of these measures has been on indigenous peoples due to the lack of available information [74]. Despite the evidence of the vulnerability of indigenous peoples to the pandemic, and the widespread recognition in the countries of the region of their individual and collective rights, including the rights to health and life, the reality is that, to date, state responses have been insufficient [75].…”
Section: The Current Situation Of Indigenous People In Latin Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary studies have found that municipalities in Latin America with a higher proportion of indigenous people presented higher infection and death rates resulting from COVID-19 (Flores-Ramírez et al 2021; Millalen et al 2020). For example, Rieger (2021) shows in her article for this special issue that the impact of COVID-19 on indigenous communities is likely underestimated given the inaccuracy of official epidemiological reports from native communities. This vulnerability is at least in part the result of these communities' limited access to healthcare services, their exposure to environmental vulnerabilities, and a general state neglect.…”
Section: Extant Inequalities and New Vulnerabilities In Latin Americamentioning
confidence: 99%
“…A pesar de la novedad del tema abordado, ya hay antecedentes de investigaciones que se han enfocado en la pandemia y municipios de tipología indígena en otras partes de México e incluso en otros países. Una de estas investigaciones es la de Bautista y Juárez (2021) quienes estudiaron el impacto de la pandemia en comunidades indígenas, tomando en cuenta la desigualdad que esta población ha padecido históricamente; otro trabajo es el de Meneses- Navarro et al (2021), el cual analizó la percepción de jóvenes indígenas de Chiapas respecto a los riesgos de la pandemia de covid-19; también, como antecedente, se tiene el estudio de Barabas (2020), quien estudió como los municipios indígenas hicieron una autogestión de la pandemia, por sus limitaciones y la desigualdad en la que han vivido; por su parte, Rieger (2021) analizó las políticas públicas que México, Bolivia y Colombia implementaron para hacer frente a la pandemia en las comunidades indígenas.…”
Section: Introductionunclassified